Strategi Komunikasi Digital dalam Meningkatkan Partisipasi Masyarakat Terhadap Program Pemerintah - Abdul Kohar; Eva Nurhaliza; Siti Ghina Rahma; Yulia Puspitasari; Riska Ferdiana (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
The development of digital technology has transformed how governments communicate with the public. Effective communication through digital media is key to increasing public participation in various government programs. This study analyzes digital communication strategies that can enhance community engagement. The use of social media, the development of digital tourism, and the dissemination of policies through digital platforms play an essential role in strengthening interactions between the government and society. Additionally, communication strategies in public transportation, the transition from analog to digital television broadcasting, and synergy in social activities also contribute to the effectiveness of government communication. An appropriate digital communication strategy should not only be informative but also interactive to build trust and enhance public engagement more effectively.